KINERJA KARYAWAN PT INDO MITRA PRATAMA DIPENGARUHI OLEH KEPEMIMPINAN MELALUI DISPILIN KERJA - Aliya Ismawati; Edy Sanusi Silitonga (Jurnal Ekonomi dan Industri, 2023)
This study aims to analyze the influence of leadership on employee performance through work discipline of PT. Indo Mitra Pratama. Analysis method using path analysis. The results of the intervening or mediation test show that the calculation can show that the value of the indirect effect through work discipline is smaller than the direct effect of leadership on employee performance. With these results it can be concluded that the work discipline variable is not capable of being a variable that mediates the influence of leadership on employee performance: a case study of PT. Indo Mitra Pratama.